Early usage of Pokémon Go and its personality correlates. (July 2017) - Tabacchi, Marco Elio; Caci, Barbara; Cardaci, Maurizio; Perticone, Valerio
Abstract: Pokémon Go is a popular augmented reality mobile game. Players find imaginary creatures by wandering into the real world, which can then be collected and used in combat. In this paper an assessment of Pokémon Go early usage in the Italian community and of its correlates with the Big Five personality traits is given. The resulting profile of early PG player is one of a more Introverted, close person with high agreeability and conscientiousness. Extraversion and Stability are positively correlated with the collection part of the game, while Agreeableness is a negative predictor thereof. Openness is correlated to the level of proficiency. Graphical abstract: Highlights: We assess Pokémon Go early usage and its correlates with the Big Five traits. Early PG player are more Introverted and Close, highly Agreeable and Conscientious. Extraversion and Stability are positively correlated with collection. Agreeableness is a negative predictor of collection. Openness is positively correlated to the level of proficiency reached in the game.